Cr(III) removal from synthetic and industrial wastewaters by using co-gasification chars of rice waste streams. (October 2018) - Dias, D.; Lapa, N.; Bernardo, M.; Ribeiro, W.; Matos, I.; Fonseca, I.; Pinto, F.
Graphical abstract: Highlights: Three major rice wastes were valorised through gasification assays. Chars were characterised for chemical, textural and ecotoxic properties. Chars and CAC were submitted to Cr(III) removal assays. Chars adsorbed and precipitated more Cr(III) than CAC in the synthetic solution. Chars precipitated more Cr(III) than CAC in the industrial wastewater. Abstract: Blends of rice waste streams were submitted to co-gasification assays. The resulting chars (G1C and G2C) were characterized and used in Cr(III) removal assays from a synthetic solution. A Commercial Activated Carbon (CAC) was used for comparison purposes. The chars were non-porous materials mainly composed by ashes (68.3–92.6% w/w). The influences of adsorbent loading (solid/liquid ratio – S/L) and initial pH in Cr(III) removal were tested. G2C at a S/L of 5 mg L −1 and an initial pH of 4.50 presented an uptake capacity significantly higher than CAC (7.29 and 2.59 mg g −1, respectively). G2C was used in Cr(III) removal assays from an industrial wastewater with Cr(III) concentrations of 50, 100 and 200 mg L −1 . Cr(III) removal by precipitation (uptake capacity ranging from 11.1 to 14.9 mg g −1 ) was more effective in G2C, while adsorption (uptake capacity of 16.1 mg g −1 ) was the main removal mechanism in CAC.